KATEMARI DIOGO ROSA: GENDER, RACE AND ETHNICS IN PHYSICS - Assis Faustino, Gustavo Augusto (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Katemari Diogo Rosa was born on October 16, 1979, in Porto Alegre. He did elementary school in a public school and high school integrated with a technical course in Secretariat, at the Federal University of Rio Grande do Sul (UFRGS). Since adolescence, she already showed affection for the area of physics. She has a degree in Physics from UFRGS, a Master in Teaching History and Philosophy of Science from the Federal University of Bahia (UFBA) and a PhD in Science Education from Columbia University. She is currently an adjunct professor at the Federal University of Bahia, where research on teaching physics and the formation of physical and physical teachers and teachers in the initial grades and discussions involving the intersectionality of gender, sexuality, race, ethnicity and socioeconomic status in the construction and science teaching.